2014
DOI: 10.1038/bjc.2014.515
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of vertical inhibition of IGF signalling using cixutumumab, an anti-IGF-1R antibody, and selumetinib, an MEK 1/2 inhibitor, in advanced solid tumours

Abstract: Background:We completed a phase I clinical trial to test the safety and toxicity of combined treatment with cixutumumab (anti-IGF-1R antibody) and selumetinib (MEK 1/2 inhibitor).Methods:Patients with advanced solid tumours, refractory to standard therapy received selumetinib hydrogen sulphate capsules orally twice daily, and cixutumumab intravenously on days 1 and 15 of each 28-day cycle. The study used a 3+3 design, with a dose-finding cohort followed by an expansion cohort at the maximally tolerated dose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…This approach might be timely for designing effective cancer treatment because previous anti-angiogenic approaches aiming to abrogate tumor blood vessel growth have had limited success (Bogdanovich et al, 2016; Ebos et al, 2009; Paez-Ribes et al, 2009; Yasuma et al, 2016). Our data could potentially have clinical implications in which anti-IGF1R antibody along with IGFBP7 agonists could be employed in conjunction with chemotherapeutic agents to block IGF1R + TSCs (Wilky et al, 2015). As such, this study might help to design effective anti-chemoresistance strategy by disrupting crosstalk between cancer stem cells and their aberrantly activated vascular niche.…”
Section: Discussionmentioning
confidence: 99%
“…This approach might be timely for designing effective cancer treatment because previous anti-angiogenic approaches aiming to abrogate tumor blood vessel growth have had limited success (Bogdanovich et al, 2016; Ebos et al, 2009; Paez-Ribes et al, 2009; Yasuma et al, 2016). Our data could potentially have clinical implications in which anti-IGF1R antibody along with IGFBP7 agonists could be employed in conjunction with chemotherapeutic agents to block IGF1R + TSCs (Wilky et al, 2015). As such, this study might help to design effective anti-chemoresistance strategy by disrupting crosstalk between cancer stem cells and their aberrantly activated vascular niche.…”
Section: Discussionmentioning
confidence: 99%
“…reported the combination to be well tolerated at maximum doses of 50 mg twice daily for selumetinib and 12 mg/kg every two weeks for cixutumumab. Six patients out of 30 achieved time to progression of >6 months, including patients with thyroid carcinoma, colorectal carcinoma and basal cell carcinoma and two patients achieved partial responses [ 53 ]. The results revealed preliminary evidence of clinical benefit and pharmacodynamic evidence of targeted inhibition with IGF-1R and MEK inhibition and which deserve further evaluation in clinical trials.…”
Section: Clinical Trials On Dual Targeted Inhibition With Mekmentioning
confidence: 99%
“…Our findings are further supported by the knowledge that mutant KRAS leads to constitutive activation of its downstream effector pathways, MAPK and PI3K, and thus, inhibiting both arms of the oncogene leads to potent antitumor effects (38 -40). Furthermore, preclinical and clinical studies focusing on the dual inhibition of MEK1/2 and IGF1R/INSR have demonstrated beneficial effects across different types of cancers (41)(42)(43)(44). Our study does not unequivocally prove the pharmacologically relevant targets of SM1-71; indeed, the functionally relevant targets of this compound are likely different in different cell types.…”
Section: Discussionmentioning
confidence: 58%